Impact of Enzymatic Degradation of the Endothelial Glycocalyx on Vascular Permeability in an Awake Hamster Model. (26th June 2012) - Landsverk, S. A.; Tsai, A. G.; Cabrales, P.; Intaglietta, M.
Abstract : Background . The inside of the endothelium is covered by a glycocalyx layer, and enzymatic degradation of this layer induces vascular leakage ex vivo . We hypothesized that enzymatic degrading of the glycocalyx in an in vivo, whole body model, would induce plasma leakage and affect the microcirculation. Methods . Golden Syrian hamsters were divided into an enzyme (hyaluronidase) and a control group. Mean arterial pressure (MAP), heart rate (HR), hematocrit (Hct), base excess (BE), and plasma volume were obtained before, 45 and 120 min after enzyme/saline treatment. Plasma volume was evaluated by the distribution volume of indocyanine green and the microcirculation by functional capillary density (FCD). The enzymatic effect was determined by measuring plasma levels of hyaluronan (HA). Results . There were no differences in MAP, HR, Hct, and BE between the two groups. Enzyme treatment did not induce changes in plasma volume but reduced FCD. There was a 50–100-fold increase in plasma HA, but no relationship was found between HA levels and plasma volume or FCD. Conclusion . Vascular leakage was not confirmed in an in vivo, whole body model after degradation of the endothelial glycocalyx. The microcirculation was affected, but no relationship between plasma levels of HA and FCD was seen.